Severe Marginal Ulcerative Keratitis Induced by an Insect Foreign Body in the Cornea. Issue 8 (August 2020) - Wang, Minshu; Wang, Haikun; Xiao, Gege; Lin, Jinyong; Wang, Wei; Li, Yingyu; Hong, Jing
Abstract : Purpose: To report an uncommon case in which an insect foreign body (FB) in the cornea induced severe marginal ulcerative keratitis. Methods: The insect body was removed during an eye examination. A shaped deep lamellar keratoplasty was then performed on the ulcerous corneal tissue and pseudopterygium. The insect FB was identified as a member of the nontoxic Diptera insect order, belonging to either the Chloropidae or Sphaeroceridae family. Results: The patient recovered well after the keratoplasty, and her corneal graft was clear with significantly improved visual acuity after 2 months. Conclusions: Long-time retention of a nontoxic insect FB in the cornea could induce severe noninfectious keratitis. Individually designed deep lamellar keratoplasty successfully restored the transparency of the cornea and visual function.